Changes in autonomic regulation due to Kangaroo care remain unaffected by using a swaddling device. (20th July 2018) - Kommers, Deedee R.; Joshi, Rohan; van Pul, Carola; Feijs, Loe; Bambang Oetomo, Sidarto; Andriessen, Peter
Abstract: Aim: To investigate the effects of a swaddling device known as the Hugsy (Hugsy, Eindhoven, the Netherlands) towards improving autonomic regulation. This device can be used both in the incubator and during Kangaroo care to absorb parental scent and warmth. After Kangaroo care, these stimuli can continue to be experienced by infants, while in the incubator. Additionally, a pre‐recorded heartbeat sound can be played. Method: Autonomic regulation was compared in preterm infants before, during and after Kangaroo care with and without the use of a swaddling device in a within‐subject study carried out in a level III neonatal intensive care unit. Descriptive statistics and effect sizes were calculated corresponding to changes in heart rate, respiratory rate, oxygen saturation, temperature and heart rate variability on intervention versus control days. Results: In this study of 20 infants with a median (interquartile range) gestational age of 28.4 (27–29.9) weeks, Kangaroo care was associated with a decrease in heart rate, respiratory rate and heart rate variability on both intervention and control days. There were no differences between intervention and control days. Conclusion: The use of an alternative swaddling device aimed at facilitating Kangaroo care did not enhance autonomic regulation, as measured by vital signs and heart rate variability.